IMPLEMENTASI PERATURAN DAERAH RENCANA TATA RUANG WILAYAH KABUPATEN BANTUL TERHADAP PERTAMBANGAN PASIR DI KAWASAN PESISIR - Bella, Helene (Jurnal Hukum Positum, 2024)
This journal is Implementation of Regional Regulations for Regional Spatial Plan of Bantul Regency on Sand Mining in Coastal Areas. This jornal aims to know and examine the implementation of the Regional Regulation of the Regional Spatial Plan of Bantul Regency on sand mining in coastal areas and how the efforts of the Bantul district government in implementing the Bantul Regulation. This research is an empirical legal research with a sociological approach to law and legislation. The source of the data is primary data, which is data obtained directly from respondents by direct interviews. The results showed that the implementation of the Regional Regulation of Bantul Regency concerning Spatial Planning on sand mining activities in coastal areas has not been optimally implemented because the spatial planning implementation process is not carried out completely and also illegal sand mining activities are still carried out in coastal areas which are protected areas.